Current state of laser synthesis of metal and alloy nanoparticles as ligand-free reference materials for nano-toxicological assays - Rehbock, Christoph; Jakobi, Jurij; Gamrad, Lisa; van der Meer, Selina; Tiedemann, Daniela; Taylor, Ulrike; Kues, Wilfried; Rath, Detlef; Barcikowski, Stephan (Beilstein Journal of Nanotechnology, 2014)
Due to the abundance of nanomaterials in medical devices and everyday products, toxicological effects related to nanoparticles released from these materials, e.g., by mechanical wear, are a growing matter of concern. Unfortunately, appropriate nanoparticles required for systematic toxicological evaluation of these materials are still lacking. Here, the ubiquitous presence of surface ligands, remaining from chemical synthesis are a major drawback as these organic residues may cause cross-contaminations in toxicological studies. Nanoparticles synthesized by pulsed laser ablation in liquid are a promising alternative as this synthesis route provides totally ligand-free nanoparticles. The first part of this article reviews recent methods that allow the size control of laser-fabricated nanoparticles, focusing on laser post irradiation, delayed bioconjugation and in situ size quenching by low salinity electrolytes. Subsequent or parallel applications of these methods enable precise tuning of the particle diameters in a regime from 4–400 nm without utilization of any artificial surface ligands. The second paragraph of this article highlights the recent progress concerning the synthesis of composition controlled alloy nanoparticles by laser ablation in liquids. Here, binary and ternary alloy nanoparticles with totally homogeneous elemental distribution could be fabricated and the composition of these particles closely resembled bulk implant material. Finally, the model AuAg was used to systematically evaluate composition related toxicological effects of alloy nanoparticles. Here Ag+ ion release is identified as the most probable mechanism of toxicity when recent toxicological studies with gametes, mammalian cells and bacteria are considered.
Keywords: albumin; gold-silver; implant alloy; laser ablation; nickel-titanium; size control; wear debris